RESOLUSI KONFLIK AGRARIA DI KAWASAN REGISTER 45 SUNGAI BUAYA (Studi Desa Talang Batu Kecamatan Mesuji Timur Kabupaten Mesuji) (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2017)
ABSTRACT. The agrarian conflict that occurred in Mesuji between PT. SIL with Talang Batu villagers isthe claiming of 7,000 hectares of land by Talang Batu villagers who were initially claimed in IUPHHK (apermit issued to utilize forest product like timber) by PT. SIL. This research focuses on the factorscausing the obstruction of agrarian conflict between PT. SIL and the community of Talang Batu Village.The purpose of this study is to analyze the handling of conflicts that have been done by the localgovernment of Mesuji and to reveal the inhibiting factors of agrarian conflicts in Mesuji settlement.The conclusion of this research showed that the factor causing the agrarian conflict started from a claimmade by Talang Batu villagers on the land area of 7000 Hectares which was initially included in IUPHHKHTI of PT.SIL. The conflict has not been resolved until now because of the unanimous agreementbetween both parties. There were two factors that hampered the conflict resolution which based onthe goals to be achieved and based on the relationship between the two parties. 45 to the initial areaestablished in the Dutch period in Besluit Lampongsche Distric. Keywords: Agrarian Conflict, Conflict Resolution Model, Registry 45